Current perspectives in healthcare computing : conference, Harrograte 20-22 March 1995 - Richards, Bernard; De Glanville, H; MacOwan, Helen; Abbott, W; Barber, B; Bryden, John S; Hayes, G. M; Jones, Ray; Kinn, Sue; Madge, Bruce; Newell, John; Peel, Victor; et al. (British Computer Society, 1995)
The book gives a review of the current state of healthcare information management and clinical uses of computers, as well as touching on the frontiers of the latest research.
Keywords: lékařská informatika; Hospital Information Systems; Medical Informatics; nemocniční informační systémy